Equestrian sport excellence stage: technical dressage in hurdle race - Inozemtseva, E. S. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to offer and test benefits of a new technical dressage model for horse hurdling applicable in the sport excellence period.